Bizarreness and Emotion Identification in Grete Stern Photomontages: Gender and Age Disparities - Rosales-Lagarde, Alejandra; Martínez-Alcalá, Claudia Isabel; Pliego-Pastrana, Patricia; Molina-Trinidad, Eva María; Díaz, José-Luis (Frontiers in Psychology, 2017)
Although the International Affective Picture System (IAPS) is used to evaluate emotions (valence, arousal, and dominance evoked by a large set of photographs), bizarre images in works of art have not been assessed with the IAPS procedures. Understood here as strange, nonsense and absurd mental contents or expressions accompanied by surprise and confusion emotions, bizarreness was assessed after healthy adult volunteers assigned this specified variable to 140 Grete Stern’s photomontages overtly intended to illustrate strange, absurd and nonsensical contents in dream reports. The images were presented to 21 Young Males (YM) and 30 Young Females (YF) who were instructed to use the IAPS Self-Assessment Manikin, along with an additional bizarre-to-normal scale, to evaluate their response to them. The valence and the bizarre-to-normal ratings showed a dissimilar pattern of distribution between genders. Ratings of scales were different, and a greater variation in scales occurred according to gender. When bizarreness was appraised, gender differences became more evident especially for YF, who rated half of the images as bizarre, and with a diminished feeling of control, while the neutral and normal images were deemed more pleased and controlled. Valence, bizarreness, and dominance formed a different component than arousal in both groups. Negative correlations between valence and dominance, and between valence and bizarreness were also found in both groups, plus a positive one for dominance and bizarreness in YF, along with curvilinear relationships among all scales. On a second experiment, 10 photomontages evaluated by YF as bizarre or as normal were administered to 18 Old Males (OM) and 28 Old Females (OF). OF´s arousal showed less neutral evaluations than OM´s. In OF the bizarre images evoked either more excitation or calmness than in OM. The distribution of the bizarre-to-normal scale was significantly different across the evaluations in YM, YF, OM and OF. The use of this extended IAPS instrument to explore bizarreness and emotional variables in response to art images seems suitable and potentially valuable to characterize bizarre, absurd, or nonsensical mental states and their brain correlates.